India's and China's Recent Experience with Reform and Growth - Tseng, Wanda (International Monetary Fund, 2005)
China and India already rank among the world's largest economies, and each is moving rapidly toward the center stage of the global economy. In this process, different priorities have been placed on economic reforms over the past two decades?China taking a more outward strategy and India, until recently, a more inward one. Can they continue to rank among the fastest-expanding economies? This volume addresses that issue, highlighting what has worked and what more needs to be done to ensure sustained rapid economic growth and poverty reduction. Addressing the two countries recent experiences with growth and reform, this book provides important insights for other developing economies. For more information on how to purchase this title, please visit http://www.palgrave.com/economics/imf/index.asp.